The Cambridge companion to Anselm - Davies, Brian (The Cambridge Companions to Philosophy, 2004)
Anselm of Canterbury (1033–1109), Benedictine monk and the second Norman archbishop of Canterbury, is regarded as one of the most important philosophers and theologians of the Middle Ages. The essays in this volume explore all of his major ideas both philosophical and theological, including his teachings on faith and reason, God's existence and nature, logic, freedom, truth, ethics, and key Christian doctrines. There is also discussion of his life, the sources of his thought, and his influence on other thinkers. New readers will find this the most convenient, accessible guide to Anselm currently available. Advanced students and specialists will find a conspectus of developments in the interpretation of Anselm.